Analysis of Supporting Tool Application Testing Generator Excitation System at Steam Power Plant - Arman Hasibuan; Rizky Almunadiansyah; Kerimzade G.S; Muhammad Daud; Fahrian Roid (CV. Akira Java Bulu, 2025)
This research aims to explore a preventive method to reduce damage to the excitation system during the startup phase of a Steam Power Plant using an Automatic Voltage Regulator (AVR). The primary objective is to enhance the efficiency and effectiveness of repair and maintenance procedures for the excitation system. A descriptive qualitative approach was employed, focusing on a generator in the steam power plant production area. The study involved defining the problem, engaging in discussions with the maintenance team, designing and testing the AVR, prioritizing the use of supporting tools during outages, and analyzing the outcomes. These processes helped identify and resolve underlying issues in the system. The study revealed a significant improvement in maintenance procedures. Previously, the average repair time for the excitation system was 8 hours, occurring approximately 10 times per year. After implementing the supporting tool and conducting tests while the unit was offline, the verification process was reduced to only 20 minutes. As a result, no damage occurred to excitation system components during gradual startup. This improvement leads to substantial cost savings—approximately IDR 4 billion—through reduced fuel consumption and more efficient use of electrical energy.